The Effect of Low Dose Oral Vitamin D on Bone Mineral Density Changes in HIV Patients: 36 Months Follow Up - Dhother, Jasreen; Bopitiya, Shyamalie; Taha, Huda; Das, Satyajit (Infectious Disorders - Drug Targets, 2020)
Background: A high incidence of vitamin-D deficiency and abnormal bone mineral density (BMD) is reported among Human Immunodeficiency Virus (HIV) infected patients. The study highlighted the effect of oral low dose vitamin-D replacement in patients with a known vitamin- D deficiency on the levels of vitamin-D [25 (OH)D], parathyroid hormone (PTH) and Bone Mineral Density (BMD) of hip and spine. Methods: Patients took a daily low dose of 800IU of vitamin-D. The following details were collected on all patients: demographics, CD-4 cell count, viral load, fracture risk factors, treatment history, corrected calcium, alkaline phosphatase (ALP), Parathyroid Hormone (PTH) (intact PTH), vitamin D 25(OH)D, inorganic phosphate and BMD of hip and spine at baseline, 12 and 36 months. Results: Our Cohort consisted of 86 patients. Patient details included: mean age 42.8 (+/-7.7) years, 48 (55%) females 64, (74%) black African, CD-4 count 440.7 (+/-180.8) cells/dL, plasma VL 1.6 log (+/-2.3) copies/mL, duration of illness 80.9 (34.1) months, duration of exposure to antiretroviral 65.2 (+/-27.9) months. At baseline, no difference in BMD of hip or spine was observed, however, a higher PTH (0.001) in patients taking Tenofivir and a lower vitamin-D was noticed in patients taking Efavirenz. After 36 months, patients on vitamin D replacement (n=44) had a significant increase in vitamin- D level (15.4 +/-10.4 vs 104.1+/-29.1 p=0.0001), lower PTH (6.3 +/-3.4 vs 4.4 +/-1.4 p=0.0001) ALP (108.9+/-78.8 vs 90.6+/-45.8 p=0.05) but no change in corrected calcium (2.13 +/-0.1 vs 2.16 +/-0.34 p=0.5) and BMD of spine (1.039+/-0.226 vs.1.027+/-0.211, p=0.77), and BMD of hip (1.020 +/- 0.205 vs. 1.039, p=0.61). In a multivariate logistic regression analysis that included all significant variables, vitamin-D replacement independently was associated with increase in vitamin- D level (OR 2.08, CI 1.03, 4.12, p=0.005), decrease in PTH level (OR 0.53, CI 0.35, 0.82, p=0.04), but not with change in corrected calcium, alkaline phosphatase, BMD of hip or spine. Conclusion: After 36 months of follow up, the replacement of low dose once daily oral vitamin-D in the treatment experienced HIV infected patients with vitamin-D deficiency can increase vitamin- D level, reduce PTH level without any change in BMD of spine and hip.
Keywords: antiretroviral therapy